Hubungan Mekanisme Koping dengan Kualitas Hidup pada Penderita Diabetes Melitus Tipe 2 di Kelurahan Nyomplong Wilayah Kerja UPTD Puskesmas Pabuaran Kota Sukabumi - Alawiyah, Luthfi; Dewi, Rosliana; Waluya, Ady (Lembaga Teewan Journal Solutions, 2026)
The quality of life for those with Type 2 Diabetes Mellitus can be affected by this chronic metabolic illness. Coping strategies are one aspect of mental health that affects life satisfaction. The purpose of this research was to look at how people living in Nyomplong Village, which is part of the UPTD Puskesmas Pabuaran working area in Sukabumi City, deal with Type 2 Diabetes Mellitus and how it affects their quality of life. This study used a cross-sectional design with quantitative correlations. Using a total sampling technique, 82 respondents were selected from a group of 85 patients. The data was collected by using the Diabetes Quality of Life (DQOL) questionnaire to evaluate quality of life and the Brief COPE Inventory to examine coping methods. The data was analyzed using a 5% significance threshold and the Chi-square test in conjunction with the contingency coefficient. The majority of respondents reported low quality of life (53.7%), and (58.5%) used maladaptive coping techniques. A good correlation (CC = 0.542) and a significant connection (p < 0.001) were seen between coping techniques and quality of life. Patients' quality of life is substantially correlated with their coping techniques in Type 2 Diabetes Mellitus. If we want to improve patients' quality of life, we must improve their adaptive coping mechanisms.